TEACHING THE SUBJECT "PROBABILITY THEORY" IN KSPI TAKING INTO ACCOUNT THE MODERN EDUCATIONAL CONDITIONS OF THE REPUBLIC OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article is devoted to some problems of teaching the theory of probability and mathematical statistics in a pedagogical institute.